Contribution Of Contemporary Tasawuf As An Alternative Solution To Overcoming Religious Spiritual Drought - Lukman, Lukman; Sopiyan, Wawan (El-Ghiroh : Jurnal Studi Keislaman, 2024)
Contemporary Sufism was bord as on of the solution for modern society in the global era, full of the problem, conflicts, problems, and spiritual, social, and moral phenomena that have hit his nation. Contemporary Sufism understanding always brings oneself closer to Allah SWT without forgetting onse’s social duties as a creature, and one lives actively and optimistically following the development of the times. Utilizing worship as medium for Sufism, a positive attitude towards life in the form of a high social ethos, a burning fighting spirit, willingness to sacrifice for the benefit of he people, and working hard. The world is something tangible as a place for devotion so that the world is valuable and mearningful. It is just that every Muslim must acknowledge and the aware of he importance of religious spirituality, which can provide peace, comfort and tranquillity. In living this life, it is necessary to synergize worldy and spiritual interests. A worldly life that pays little attention to spiritual and religious feelings can lead to a materialistic-hedonistic and consumeristic personality contemporary Sufism bridges the balance between the demands of physical needs while simultaneously providing spiritual needs and reviving religious/spiritual feelings.